MODEL AGROFORESTRI UNTUK PENYANGGA EKOSISTEM DI LERENG SELATAN TAMAN NASIONAL GUNUNG MERAPI - Suryanto, Priyono; Soemardi; Yuslinawari (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2018)
The study aims to determine the characteristics of the distribution pattern of vegetation, and landscape perimeter TN southern slopes of Mount Merapi.The results showed that land cover by vegetation is 59.25% of the overall patch of landscape. Model agroforestry being developed in the third patch regions of southern slopes TNGM dominated by â€œtegalanâ€ and homegarden pattern. Identification of agroforestry landscape models currently on ecological density range called Ecological Density accupying to 336.38 m/Ha. SDI (Shannon Diversity Index) by spatial model is of 0.98. While the actual SDI conditions based on groundcheck has a mean value of 1.7. Scoring agroforestry model based of ecological functions and economic values obtained optimum value the model agroforestry are field and homegarden as agroforestry practices. Keywords: Agroforestry, Silviculture, and Landscape